Hepatocellular carcinoma treated with anti-epidermal growth factor receptor antibody nimotuzumab: A case report. Issue 39 (September 2017) - Song, Peng; Yang, Jing; Li, Xiaomei; Huang, Haili; Guo, Xueguang; Zhou, Gang; Xu, Xian; Cai, Yi; Zhu, Min; Wang, Peng; Zhao, Shu; Zhang, Dong
Abstract: Rationale: Molecular targeted therapy provides new ideas and hope for the treatment of hepatocellular cancer. Epidermal growth factor receptor (EGFR) is closely related to tumor cell proliferation, apoptosis, invasion, and metastasis. Patient concerns: Several reports indicate that the EGFR is expressed frequently in hepatocellular carcinoma (HCC), thus targeting EGFR research has become a hot topic to explore the treatment of HCC patient. Diagnoses: Anti-EGFR might serve as a potential therapeutic agent, especially for patients with HCC who are unable to tolerate chemotherapy and surgery. Interventions: Although phase II open-label study of cetuximab in unresectable HCC was negative, the clinical relevance of this report by Song et al which is based on a single patient is questionable. Outcomes: We for the first time report that nimotuzumab (an anti-EGFR mAb) resulted in a complete remission (CR) in an 87-year-old patient with HCC. The patient was in B stage according to Barcelona center staging criteria and his liver function was Child-Pugh B grade. Lessons: Our case suggested that anti-EGFR mAbs might be potential therapeutic options for HCC.